Potential use of music therapy elements in music teaching - Metić, Martina (Array, 2020)
Recent scientific studies have shown that involving children in music activities influences their mental, emotional, and social development; music is, thus, being used increasingly for medical and therapeutic purposes. In order to discover whether some elements of particular methods of music therapy can be applied in music teaching in primary schools, we conducted a qualitative research in which the participants were third-year elementary school pupils in Osijek. To collect the data, we used a systematic observation procedure. Data analysis involved both qualitative and quantitative analyses. The research results show that the introduction of elements of certain methods of music therapy is possible and that pupils are happy to participate in all the activities carried out. In doing so, pupils demonstrate imagination, creativity, independence at work, and willingness to cooperate.